Services needed and received when moving on from permanent supportive housing. Issue 1 (2nd January 2022) - Tiderington, Emmy; Goodwin, Jordan M.; Reyes, Laurent; Herman, Daniel
ABSTRACT: Moving On initiatives present opportunities for stable individuals to move from permanent supportive housing (PSH) into mainstream affordable housing. However, there is a dearth of research on how best to support individuals during this critical transition. This mixed-methods study examines transitional and aftercare services needed and received by individuals moving on through an MOI. Descriptive statistics quantified frequency of services needed and received as reported by movers ( n  = 43) in a post-move survey. Movers ( n  = 25) also completed pre- and post-move qualitative interviews regarding the transition and thematic analysis was used to elucidate how and why various supports were helpful to movers. During the pre-move transition, housing navigation and help obtaining financial assistance were the most frequently needed services. Movers relied on informal family and peer support to supplement provider assistance in these areas. Case manager visits were the most frequently needed aftercare service and financial assistance was the greatest unmet post-move need. In both periods, formal peer support was an identified service gap. This MOI generally met the self-identified needs of movers. However, MOIs may benefit from better targeting and more robust services specific to housing discrimination, tenants' rights, formal peer support, and financial assistance.